The archaeology of refuge and recourse Coast Miwok resilience and indigenous hinterlands of colonial California - Schneider, Tsim D., 1979- (Archaeology of indigenous-colonial interactions in the Americas., 2021)
"As an Indigenous scholar researching the history and archaeology of his own tribe, Tsim D. Schneider provides a unique and timely contribution to the growing field of Indigenous archaeology and offers a new perspective on the primary role and relevance of Indigenous places and homelands in the study of colonial encounters"--